Historical and future projected costs of capital for ten energy technologies across 176 countries - Hatton,L; Staffell,I; Oluleye,G; Jansen,M; Hawkes,A (Scientific Data, 2025)
Accelerating the deployment of clean generation technologies will be key to achieving global climate targets, yet accurately modelling the financial conditions they face is challenging. The cost of capital (or discount rate) is a key input for energy system models, which are used widely to explore future decarbonisation scenarios. Despite its importance, data on the cost of capital is typically outdated, closed-source and geographically concentrated. Even for countries with substantial technology deployment, accessing empirical data can be difficult, leading to the use of standard assumptions in modelling which can substantially bias results (due to the high capital intensity of clean technologies). Here, we provide estimates of the cost of capital for 10 generation technologies at a national level (including solar, wind, bioenergy, and natural gas with carbon capture) for 176 countries, for 2015 to 2030 spanning 27,640 data points. An interactive web tool available at wacc-forecaster.streamlit.app has also been produced to visualise estimates for given years, countries and technologies, making results more accessible to a range of audiences.